Investigation The Effect of Leadership and Work Environment on Employee Performance - Suarni Norawati; Feri Irawan; Citrawati Jatiningrum (Fakultas Bisnis, 2022)
This study aims to investigate the effect of leadership and work environment on employee performance. The research sample are 102 employees of the Regional Water Company (PDAM) Tirta Kampar, Kampar Regency. Using the secondary and primary data, analysis method using statistics tool multiple linear regression The results reveal that leadership and work environment both partially and simultaneously have a positive effect on the employees’ performance. The result also show that directly effect of leadership variables and work environment on performance is greater than the indirectly effect of leadership and work environment on performance through job satisfaction.